(untitled) (Asian Journal of Social Science Studies, 2019)
The Jesuits began their missionary work in Asia in the 16th century. After the missions in India and Japan, they tried to enter China and spread Catholicism at the end of the 16th century (Note 1). Due to the special political and cultural environment of China at that time, the missionary experience of Jesuits in India and Japan did not fully apply to Chinese society, which caused their missionary process to be rocky (Note 2). In order to adapt to the different environment of the Ming dynasty, Jesuits had to actively adjust their missionary strategies. After a period of observation and exploration, Jesuits used a missionary method of preaching through books in Ming and Qing dynasties (Note 3). Therefore, the adjustments of their missionary strategies are also reflected in their Chinese missionary works, including the adjustments of Jesuits’ evaluation of Buddhism in their Chinese missionary works, which is a question worthy of attention and research.